Assessing the uncertainty in central banks' inflation outlooks - Malte Knüppel; Guido Schultefrankenfeld (Deutsche Bundesbank, 2018)
Recent research has found that macroeconomic survey forecasts of uncertainty exhibit several deficiencies, such as horizon-dependent biases and lower accuracy than simple unconditional uncertainty forecasts. We examine the inflation uncertainty forecasts from the Bank of England, the Banco Central do Brasil, the Magyar Nemzeti Bank and the Sveriges Riksbank to assess whether central banks' uncertainty forecasts might be subject to similar problems. We find that, while most central banks' uncertainty forecasts also tend to be underconfident at short horizons and overconfident at longer horizons, they are mostly not significantly biased. Moreover, they tend to be at least as precise as unconditional uncertainty forecasts from two different approaches.
Keywords: C13; C32; C53; 330; Density Forecasts; Fan Charts; Forecast Optimality; Forecast Accuracy